Analisis Inovasi Pelayanan Pajak Daerah melalui Aplikasi EPPSON (Elektronik Pembayaran Pajak Daerah Aplikasi Solo Destination) di Kota Surakarta - Olivia Tyas Ardianti; Wahid - Abdulrahman (Journal of Politic and Government Studies, 2020)
To improve the quality of public service. Service innovation is key to the successful implementation of e-government. The innovation that is developing in Indonesia is the application of smartcity. Surakarta became one of the cities that implemented the concept of innovation, one of which is in the field of local tax services, urakarta city innovates by launching eppson feature (Electronic payment of Regional Tax Solo Destination Application) to facilitate the people of Surakarta city get local tax service. This research uses qualitative descriptive methods with data collection techniques in the form of interviews and documentation. Data obtained from Surakarta City Council, especially BPPKAD and eppson application users, then the data obtained is analyzed using theory and data source to answer the formulation of the problem that has been outlined From the results of the research analysis found that the implementation of regional tax service innovation through EPPSON application in Surakarta city managed to increase local tax receipts and also improve taxpayer compliance to pay its obligations. It was also found in the research that taxpayers feel helped by the innovation of local tax services through this EPPSON application, such as the ease of service provided, only through smartphones can be done services anytime and anywhere. But unfortunately the innovation of this local tax service in its management still lacks quality human resources or who do understand about it, so that local government must continue to improve the quality of human resources to develop innovation of local tax services in order to be even better. So it can be concluded that the innovation of this local tax service includes success in improving the quality of service, by making it easier for taxpayers to be able to pay their obligations as a taxpayer, thus the innovation of this local tax service is accepted by the people of Surakarta city and recognized that the innovation of this local tax service makes it easier for its users to pay taxes wherever and whenever. So the government must improve the quality and quantity of human resources in order to develop the innovation of tax servants to be better.